The effectiveness of medical student wellbeing workshop for stress management of medical students, school of medical sciences, USM - Yusoff, Muhamad Saiful Bahri (Pusat Pengajian Kesihatan, 2015)
Many researchers have emphasized the importance of teaching stress management and self-care skills to medical students as they are vulnerable to develop health problems related to physical, mental and behavior. A 4-hour medical student wellbeing intervention was designed based on the DEAL model to address these problems. A randomized controlled trial study was conducted on 171 medical students. They were randomly allocated into intervention and control groups. Their stress, anxiety, depression, coping strategies and perceived academic stress were measured by validated tools at five different intervals; at 2 weeks before the intervention, and at 1 week, 8 weeks, 16 weeks and 32 weeks after the intervention. The repeated measure ANCOVA was applied to determine the effect of intervention across the five intervals. A total of 153 medical students (intervention = 73 and control = 80) completed this study. Between group analysis showed that the intervention group significantly experienced lower stress (p = 0.009) and depression (p = 0.013) symptoms, less frequent of denial (p = 0.002), less frequent of self-blame (p = 0.002) and lower perceived academic stress (p = 0.009) than the control group. The results support the positive impacts of the DEALbased intervention on the medical students’ wellbeing. It is a promising intervention to be adopted by higher education as it consumes minimal amount of time, money, training and man power as well as simple to be implemented.